Azo dye aggregates and their roles in the morphology and conductivity of polypyrrole. (June 2020) - Li, Yu; Wang, Yanping; Bian, Cheng; Stejskal, Jaroslav; Zheng, Yuansuo; Jing, Xinli
Abstract: Polypyrrole (PPy) synthesized by the oxidation of pyrrole with iron(III) chloride in the presence of sulfonic azo dyes exhibits fascinating nanometer-scale morphology and high conductivity, which are distinctly different from their counterparts prepared without dyes. The present work systematically studied the roles of sulfonic azo dye aggregates formed in acidic medium during the growth of PPy based on structural and elemental analysis. The formation of PPy nanostructures have been investigated by following the pH profile, by adjusting the precipitation rate of dye aggregates and by comparing the molecular structure of three azo dyes, viz. methyl orange, ethyl orange and Orange I. The results showed that the ethyl orange derived aggregates formed in iron(III) chloride solution and in hydrochloric acid solution had exactly the same structure as well as elemental composition. Aggregates derived from methyl orange formed in iron(III) chloride solution involved a trace amount of iron element. Orange I, another azo dye that can induce aggregates rapidly in iron(III) chloride solution, contributed negligibly to both the morphology and conductivity of PPy. The structure-directing effects of methyl orange/iron(III) complexes in directing PPy nanostructures seems to be unique and cannot be simply extended to other azo dyes, probably due to the dye interaction with iron ions. Graphical abstract: Image 1 Highlights: Methyl orange and ethyl orange behave differently in iron (III) chloride solution. Morphology and precipitation rate of dye aggregates both affect PPy growth. Orange I induces PPy nanofibers while contributes negligibly to their conductivity. Methyl orange/iron (III) complexes work uniquely on PPy compared to other azo dyes.